Case exemplars of how academic libraries promote sustainable communities - Tribelhorn, Sarah K.; Mehra, Bharat (Emerald Publishing Limited, 2026)
This is an edited collection of sustainability efforts in academic libraries, partnering with various types of institutions and organizations, including libraries from higher education that are public or private, research universities, degree-awarding or vocational, among others. This volume includes research, case studies, and reflective narratives from academic libraries and their collaborations working with varied partners toward operationalizing the United Nations' (UN) Sustainable Development Goals (SDGs). This collection offers valuable insight into how academic library partnerships, both direct and indirect, contribute to sustainability efforts, with a focus on social equity, economic feasibility, and environmental stewardship to nurture community resilience. Structured into five sections, it highlights the global impact of academic libraries and their partners in adopting and implementing the SDGs to drive social change. These sections specifically explore how libraries are: serving the mission of higher education, extending education to sustainable cities, becoming embedded in communities, forming partnerships for greater impact, and achieving cross-cutting impacts across various initiatives. These insightful chapters include innovative strategies and global perspectives on some of the cutting-edge work initiated and/or led by academic libraries to build sustainable and resilient communities, through collaborative ventures and out-of-the-box partnerships.
Includes index.
Keywords: Sustainable development.; Academic libraries.; Language Arts & Disciplines -- Library & Information Science -- General.; Library, archive and information management.; Library and information services.; elektronické knihy; electronic books